Speech enhancement hybrid of wiener filter and haar wavelet algorithm using DSP / \c May Myat Noe Aye. - Aye, May Myat Noe (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The main objective of this project are ; to enhance and reduce the noise from speech signal and implement on floating point DSP processor ; to develop the enhancement system by using adaptive wiener filter hybrid with haar wavelet algorithm ; to validate the result Peak-Signal-to-Noise-Ratio measurement will be used.